PERBEDAAN MOTIVASI MENGAJARANTARA GURU YANG SUDAH BERSERTIFIKASI DENGAN GURU YANG BELUM BERSERTIFIKASI DI SEKOLAH MENENGAH KEJURUAN (SMK) 7 DAN 8 NEGERI KOTA PADANG - Mukhtar Abdul Rasyid (Universitas Negeri Padang, 2014)
The research was conducted by a temporary problem that shows that there is no significant difference between the motivation of teaching held by teachers who are already certified to teach motivation that a teacher who is not certified . This study aims to determine the level of motivation to teach the difference between a teacher who has been certified by a certified teacher who has not thought daari observations while there was no difference between the motivation of teachers who are already certified to teach by teaching motivation of teachers who have not certified . This research is descriptive research that reveals a situation as it is. The population in this study are already certified teachers and teachers who have not been certified in puff Vocational School ( SMK ) Padang State with 60 certified teachers and 60 teachers were not certified (after sampling ) . Data collection tool was a questionnaire . Results show trial questionnaire is valid and reliable questionnaire . With the results obtained for certified teachers rhitung > rtable = 0.973 > 0.648 . And to reliably obtained results rhitung ( 0.669 ) > rtabel ( 0.632 ) , because rhitung > rtabel then the result unreliable . Furthermore, for teachers not certified the results obtained rhitung ( 0.967 ) > rtabel (0.648 ) , because rhitung > rtabel then the result is valid , and to reliably obtained results rhitung ( 0,803 ) > rtabel ( 0.632 ) , then the result is reliable . Data were analyzed by calculating the mean . The results showed bersertifkasi motivation of teachers to teach and teachers alike have not been certified to be in good category with an average of 4.01 and 3.91 . Testing homogeneity , after the sample variance homogeneity test showed homogeneous and Ho is accepted , the results Ftabel (1.008 ) < F table ( 1.54 ) . Test T -test , T - test after test results show tcount ( 32.11 ) < t table ( 55.86 ) , it means that there is no difference between the motivation of teachers who are already certified to teach with teachers who have not been certified. Kata Kunci: Motivasi Mengajar